2022
DOI: 10.1101/2022.10.27.514125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug Reinforcement Impairs Cognitive Flexibility by Inhibiting Striatal Cholinergic Neurons

Abstract: The mechanisms underlying the reduction in cognitive flexibility associated with reinforcement of addictive substance use are unknown. This reinforcement is mediated by substance-induced synaptic plasticity in direct-pathway medium spiny neurons (dMSNs) that project to the substantia nigra (SNr). Cognitive flexibility is mediated by cholinergic interneurons (CINs), which receive extensive local inhibition from the striatum. Here, we report that cocaine or alcohol administration caused a long-lasting potentiati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 71 publications
2
7
0
Order By: Relevance
“…We hypothesize that it is triggered by GABA release from D1-MSNs during reward-acquiring actions, with supporting evidence from our observation that D1-MSN optogenetic activation can induce a pauserebound in CIN firing [39]. The subsequent ACh increase may have dual origins: pauserebound firing of CINs [25,39] and thalamic CIN activation [27,30]. The following ACh dip might arise from another CIN firing pause, often seen in post-thalamic activation [27,65].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…We hypothesize that it is triggered by GABA release from D1-MSNs during reward-acquiring actions, with supporting evidence from our observation that D1-MSN optogenetic activation can induce a pauserebound in CIN firing [39]. The subsequent ACh increase may have dual origins: pauserebound firing of CINs [25,39] and thalamic CIN activation [27,30]. The following ACh dip might arise from another CIN firing pause, often seen in post-thalamic activation [27,65].…”
Section: Discussionsupporting
confidence: 79%
“…3D) for pause disruption. We then used a reversal learning paradigm [37, 39] to uncover behavioral impacts. In this setup, animals initially associate a left lever with sucrose and a right lever with food pellets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have suggested that CINs play a crucial role in regulating the activity of MSNs and dopamine transmission in the NAcSh, which is a key brain region involved in alcohol consumption (Kolpakova et al., 2022). Conversely, alcohol and other addictive substances have been shown to interact with cholinergic neurons in different brain regions, including NAc, to cause impairment in behaviors, such as learning and cognition (Bariselli et al., 2023; Gangal et al., 2023; Ma et al., 2022; Smiley et al., 2021; Yorgason et al., 2022). However, the direct causal relationship between CINs and alcohol consumption remains unclear.…”
Section: Discussionmentioning
confidence: 99%